Constraints over the age of magmatism and subsequent deformation for the Neoarchean Kukkola Gneiss Complex, northern Fennoscandia - Pietari Skyttä; Maiju Määttä; Simo Piippo; Jaakko Kara; Asko Käpyaho; Esa Heilimo; Hugh O'Brien (GEOLOGICAL SOC FINLAND, 2022)
The Archean crust in northern Fennoscandia preserves a fragmentary geological record, making direct correlation among Archean domains challenging. This study presents two new zircon U-Pb age determinations from the Archean Kukkola Gneiss Complex (KGC) that straddles the border between Finland and Sweden. The results indicate that crystallization of tonalites within the magmatic core of the complex occurred at 2711 +/- 8 Ma, somewhat earlier than previously considered. A new pulse of magmatism occurred at 2675 +/- 10 Ma as demonstrated by hornblende-tonalites cutting the 2.71 Ga rocks. The results further indicate that the first deformation event responsible for development of penetrative foliations occurred after the first magmatic event at 2.71 Ga and prior to the subsequent tectonothermal event at 2.68 Ga. These findings are in concert with the known major periods of magmatism (2.8-2.7 Ga) and deformation (2.7 Ga) within better-known Archean domains in northern Fennoscandia, and hence support their correlation with KGC. Three complementary age determinations on the Haparanda-suite granites and tonalites were conducted: the results indicate crystallization ages of 1.90-1.89 Ga, overlapping with the known age range of the suite and supporting its predominance over the 1.8 Ga Lina suite granites in the Tornio-Haparanda area.